Cultural Imperialism and Jean Rhys’s Heroine: between the British and the Caribbean - Miksza, Agnieszka (The British Empire: Interdisciplinary Deliberations, 2019)
Jean Rhys’s life, as well as the lives of her heroines can be summarized as “trying to belong and failing”. The concerns addressed by Jean Rhys oscillate between power and powerless, discourse and silence, prisoners, patients, and the “machinery that keeps society functioning”. All these are a crucial contextual frame for Rhys’s most important themes, which are psychological implications of the cultural dualism, which can be both ascribed to Jean Rhys and her fictional heroines.